Can Scanning Technique and Mastery of The Vocabulary Affect Students’ Reading Proficiency? (Case Study at Junior Secondary School in Purwakarta) - Robby Wahyudi (Jurnal Pendidikan Indonesia, 2024)
The objective for this article is for understanding whether the scanning technique and mastery of the vocabulary can affect students’ reading proficiency at Junior Secondary School in Purwakarta. Research methodology used was experiment. Samples were taken with random technique from 40 students; half of them were in conventional group/class and the rest were in the experiment group/class. From the outcome, it is concluded that scanning, as one of the methods taught in reading comprehension, could affect the students’ proficiency as well as the mastery of vocabulary. However, when the variables are combined, it was concluded that they could not affect the proficiency significantly. Since most exams of the English lesson in school use reading comprehension, teaching technique in understanding text such as scanning needs to be taught for the students to do the tests efficiently for the time given is limited. Hopefully, with the improvement of the vocabulary mastery, students can reach their competency in reading proficiency.